Doing good does you good? The financial impact of individual CSR dimensions: A Malaysian context - Tan, K.L.; Ho, Jie Min; Pidani, R.; Goveravaram, A.D. (2021)
Purpose: Although corporate social responsibility–corporate financial performance (CSR-CFP) research topics have been widely investigated, previous research has yet to examine the relationship between the specific dimension of CSR and CFP among Malaysian public-listed companies. Through literature review, it has been found that the CSR-CFP studies conducted in Malaysia have omitted the role of workplace diversity dimension in contribution to CFP. Failure to consider this variable may risk misrepresenting the relationship between CSR and CFP, thereby preclude consensus on the direction of the relationship between the variables. The purpose of this study is to investigate the relationship between individual CSR dimensions and CFP. Design Methodology Approach: By using the CSR dimension disclosure-scoring method and cross-sectional data analysis, this research has conducted a content analysis on annual reports of the sample companies to evaluate the influence of CSR practices on companies’ profitability during 2015. Findings: The results show that companies displaying CSR behavior are associated with higher CFP. That is to say, there is a positive relationship between CSR and CFP. However, the result has further revealed that the five CSR dimensions in isolation would differently associate with the two proxies of CFP. Originality Value: To the best of the authors’ knowledge, this is the first study in Malaysia that considers workplace diversity issues as one of the dimensions of CSR. The findings will thus bring new insights into CSR application in Malaysia and its association with the CFP.